Effects of reducing sedentary behaviour on renal glucose uptake during insulin stimulation: A post‐hoc analysis of a 6‐month randomized controlled trial - Rebelos, Eleni; Dadson, Prince; Sjöros, Tanja; Laine, Saara; Norha, Jooa; Garthwaite, Taru; Löyttyniemi, Eliisa; Eskola, Olli; Koivumäki, Mikko; Vähä‐Ypyä, Henri; Sievänen, Harri; Vasankari, Tommi; et al. (John Wiley & Sons, 2026)
Aims
Obesity is an independent risk factor for chronic kidney disease, and weight loss interventions lead to better kidney outcomes. We aimed to assess whether reducing sedentary behaviour in patients with metabolic syndrome impacts renal glucose uptake rate (GU) during insulin stimulation.
Materials and Methods
Forty-four participants with metabolic syndrome were randomized to receive either guidance to reduce sedentary behaviour (INT) by 1 h/day during a 6-month intervention or to maintain usual sedentary behaviour (CONT). For this post-hoc analysis, we included all participants with available renal data: 34 participants at baseline and 30 at the end of the intervention. Participants underwent 18F-fluorodeoxyglucose positron emission tomography ([18F]FDG-PET) during a hyperinsulinemic clamp at baseline and at 6 months. Renal [18F]FDG-PET data were analysed using fractional uptake rate (FUR). A correction for the estimated residual amount of [18F]FDG inside the tubuli was applied. Corrected GU was calculated as the product of FUR and glycemia.
Results
At the study end, light and moderate-to-vigorous physical activity (PA) were increased and BMI was slightly decreased, with no significant intervention effect. Cortical and medullary GU increased vs baseline, similarly in both groups. At baseline, cortical GU was directly related to the degree of insulin sensitivity and inversely to BMI and circulating FFA levels. Change in renal GU was directly related to change in liver GU, but not to the change in whole-body insulin sensitivity.
Conclusions
In patients with metabolic syndrome, insulin-stimulated renal GU increases concomitantly with a small decrease in body adiposity, independently of changes in whole-body glucose disposal.